1998
DOI: 10.1182/blood.v92.9.3163
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Gene Transfer to Human Hematopoietic SCID-Repopulating Cells Under Serum-Free Conditions

Abstract: Stable gene transfer to human pluripotent hematopoietic stem cells (PHSCs) is an attractive strategy for the curative treatment of many genetic hematologic disorders. In clinical trials, the levels of gene transfer to this cell population have generally been low, reflecting deficiencies in both the vector systems and transduction conditions. In this study, we have used a pseudotyped murine retroviral vector to transduce human CD34+ cells purified from bone marrow (BM) and umbilical cord blood (CB) under optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 61 publications
6
26
0
Order By: Relevance
“…32 The results shown here suggest that a limited gene transfer efficiency in the engineered graft may be sufficient to achieve protection from lethal hematotoxicity in clinical trials. Similar, if not increased, gene transfer efficiency compared to that seen in the present study has recently been reported from primate models of retroviral gene transfer, 33,34 as well as in repopulating human BM cells that have been analyzed as xenografts in immunodeficient mice, 28,35,36 and also in a clinical study. 20 The moderate transduction rate obtained in the present mouse model therefore indicates that SF1m might also be effective in human gene therapy.…”
Section: Discussionsupporting
confidence: 90%
“…32 The results shown here suggest that a limited gene transfer efficiency in the engineered graft may be sufficient to achieve protection from lethal hematotoxicity in clinical trials. Similar, if not increased, gene transfer efficiency compared to that seen in the present study has recently been reported from primate models of retroviral gene transfer, 33,34 as well as in repopulating human BM cells that have been analyzed as xenografts in immunodeficient mice, 28,35,36 and also in a clinical study. 20 The moderate transduction rate obtained in the present mouse model therefore indicates that SF1m might also be effective in human gene therapy.…”
Section: Discussionsupporting
confidence: 90%
“…In the PG13‐MGIN SF group, all mice were engrafted with marked human cells and the mean level of marking was just below 50%, while more than 50% of human colonies derived from the bone marrow of NOD/SCID mice were GFP‐positive. This level of gene transfer to SRCs is superior to what has been reported by other investigators using GALV‐pseudotyped or amphotropic vectors5–9, 37, 38 and also slightly higher than the transduction efficiency recently reported for an oncoretroviral vector pseudotyped with the RD114 envelope39. In the latter study, Kelly et al .…”
Section: Discussionmentioning
confidence: 50%
“…Several studies have shown that serum‐free transduction of CD34 + cells with repopulating capacity using GALV‐pseudotyped vectors is feasible5, 7. However, no side‐by‐side comparison using a GALV‐pseudotyped vector with and without serum for the transduction of repopulating cells has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of LNGFR provirus in NOD/SCID BM was determined by polymerase chain reaction (PCR) amplifying the specific 425-bp fragment of the LNGFR gene [35].…”
Section: Polymerase Chain Reaction For Human Lngfrmentioning
confidence: 99%